ChemInform Abstract: Regioselectivity Switch in Chiral Amine‐Catalyzed Asymmetric Addition of Aldehydes to Reactive Enals. Issue 42 (October 2015) - Kano, Taichi; Maruyama, Hiroki; Sakamoto, Ryu; Maruoka, Keiji
Abstract 1, 2‐ or 1, 4‐addition of aldehydes to enals can be controlled by the choice of catalyst.